Simulasi Penanganan Bencana Terpadu dengan Fokus pada Pertolongan Pertama di SDN 1 Sawotratap Kecamatan Gedangan Kabupaten Sidoarjo - Nurul Fathiyyah; Ainun Ganisia; Rakhmalia Imeldawati (Rena Cipta Mandiri, 2025)
Indonesia is a disaster-prone country due to its location within the Pacific Ring of Fire. This condition requires communities, including school-age children, to have basic preparedness and first aid skills in emergency situations. Elementary school students need to be equipped with knowledge and practical skills in first aid to provide initial assistance before professional help arrives. This community service program aimed to improve the knowledge, preparedness, and practical skills of students at SDN 1 Sawotratap, Gedangan District, Sidoarjo Regency, in integrated disaster management with a focus on first aid. The program was conducted through needs analysis, partner coordination, interactive education, demonstration, integrated disaster simulation, skill observation, and evaluation using pre-test and post-test methods. The results showed an improvement in students’ knowledge of first aid and disaster evacuation procedures. After the intervention, the average knowledge score increased by 80% regarding the recognition of basic medical equipment, wound dressing techniques, and self-evacuation procedures. Students were also able to practice basic first aid techniques through simulation and showed calmer responses when facing disaster scenarios. This program also produced a draft pocket guide on disaster first aid as a sustainable educational medium for the school. Integrated disaster management simulation focusing on first aid is an effective practical education strategy to improve elementary school students’ preparedness. This activity is expected to serve as a school-based empowerment model in developing young generations who are disaster-aware and capable of acting as first responders in school and family environments.